2015
DOI: 10.1016/j.jhealeco.2015.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Fear itself: The effects of distressing economic news on birth outcomes

Abstract: I use new administrative data on mass layoffs and plant closings to study the effects of distressing economic news. Exposure to stressful events during pregnancy can impair fetal development. I find that announcement of impending job losses leads to a transient decrease in the mean birth weight within the firm's county 1-4 months before the job losses. A loss of 500 jobs corresponds roughly to a decrease of 15-20 grams and 16 percent greater risk of low birth weight. Further analyses show that the initial effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 91 publications
1
64
0
Order By: Relevance
“…The most rigorous study of birth outcomes found that the announcement of mass layoffs (an indicator of fear or stress related to the economy) was associated with declines in birthweight even prior to actual layoffs [17]. Evidence from Spain suggested that maternal educational inequalities in adverse birth outcomes may have increased during the Recession [18].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most rigorous study of birth outcomes found that the announcement of mass layoffs (an indicator of fear or stress related to the economy) was associated with declines in birthweight even prior to actual layoffs [17]. Evidence from Spain suggested that maternal educational inequalities in adverse birth outcomes may have increased during the Recession [18].…”
Section: Resultsmentioning
confidence: 99%
“…Fertility declined primarily among younger women [1416]. Less vulnerable groups, such as those who remained employed [30, 31], still experienced negative health impacts of the Recession, suggesting a possible role of stress and uncertainty apart from actual job, income, or housing loss [17, 90]. Evidence from the E.U.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our focus on sex differences follows that of Skoufias and Vinha (2012), and our attention to the exact timing of exposure follows Andalon et al (2014) and Carlson (2015), among others, building on previous work in South Asia using Demographic and Health Surveys (DHS) in both India and Nepal that suggest a stronger link between rainfall variation and child height during early months in infancy than during other periods of a child’s life (Lokshin and Radyakin, 2012, Tiwari et al, 2013). Moreover, focusing on the growing seasons in Nepal, other researchers find that anomalies in vegetation density show higher correlations with stunting during the in utero and infancy phases than in other phases of a child’s development (Shively et al, 2015).…”
Section: Background and Identification Strategymentioning
confidence: 99%
“…This paper expands on the previous literature by using quarterly variation in NDVI to identify sex-specific differences in the timing of vulnerability before and after birth, and to test for the possible protective effects of improved sanitation and food markets. Our focus on sex differences follows that of Skoufias and Vinha (2012), and our attention to the exact timing of exposure follows Andalon et al (2014) and Carlson (2015), among others, building on previous work in South Asia using Demographic and Health Surveys (DHS) in both India and Nepal that suggest a stronger link between rainfall variation and child height during early months in infancy than during other periods of a child's life (Lokshin and Radyakin, 2012;Tiwari et al, 2013). Moreover, focusing on the growing seasons in Nepal, other researchers find that anomalies in vegetation density show higher correlations with stunting during the in utero and infancy phases than in other phases of a child's development (Shively et al, 2015).…”
Section: Vulnerability In Utero and After Birthmentioning
confidence: 99%